5x-2-5x=600
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(5x-1\right)^2+2\left(1-5x\right)\left(4+5x\right)+\left(5x+4\right)^2\)
\(=\left(5x-1\right)^2-2\left(5x-1\right)\left(5x+4\right)+\left(5x+4\right)^2\)
\(=\left[\left(5x-1\right)-\left(5x+4\right)\right]^2\)
\(=\left(5x-1-5x-4\right)^2\)
\(=\left(-5\right)^2\)
\(=25\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2x = 64
=> 2x = 26
=> x = 6
b) 5x = 7x
=> 7x - 5x = 0
=> 5x(2x - 1) = 0
=> \(\orbr{\begin{cases}5^x=0\\2^x-1=0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x\in\varnothing\\2^x=1\end{cases}}\)\(\Rightarrow2^x=2^0\Rightarrow x=0\)
c) 5x . 53 = 125
=> 5x + 3 = 53
=> x + 3 = 3
=> x = 0
d) 3x - 17 = 64
=> 3x = 64 + 17
=> 3x = 81
=> 3x = 34
=> x = 4
e) (3x - 5)3 = 52 . 24 + 600
=> (3x - 5)3 = 25.16 + 600
=> (3x - 5)3 = 400+ 600
=> (3x - 5)3 = 1000
=> (3x - 5)3 = 103
=> 3x - 5 = 10
=> 3x = 15
=> x = 15 : 3
=> x = 5
g) (5x - 15)3 = (5x - 15)7
=> (5x - 15)7 - (5x - 15)3 = 0
=> (5x - 15)3. [(5x - 15)4 - 1] = 0
=> \(\orbr{\begin{cases}\left(5x-15\right)^3=0\\\left(5x-15\right)^4-1=0\end{cases}\Rightarrow\orbr{\begin{cases}\left(5x-15\right)=0\\\left(5x-15\right)^4=1\end{cases}\Rightarrow}\orbr{\begin{cases}5x-15=0\\5x-15=\pm1\end{cases}}}\)
Nếu 5x - 15 =0
=> 5x = 15
=> x = 3
Nếu 5x - 15 = 1
=> 5x = 16
=> x = 16 : 5
=> x = 16/5
Nếu 5x - 16 = -1
=> 5x = 14
=> x = 14 : 5
=> x = 14/5
Vậy \(x\in\left\{3;\frac{16}{5};\frac{14}{5}\right\}\)
a) 2x = 64
Vì 26 = 64 nên x = 6
Vậy x = 6
b) 5x = 7x
Vì 50 = 1 và 70 = 1
=> x = 0
Vậy, x = 0
c) 5x . 53 = 625
Ta có 625 = 54
nên 5x . 53 = 54
5x+3 = 54
=> x = 1
Vậy x = 1
d) 3x - 17 = 64
3x = 64 + 17 = 81 = 34
=> x = 4
Vậy x = 4
e) ( 3x - 5 ) 3 = 52 . 24 + 600
( 3x - 5 ) 3 = 25 . 16 + 600 = 1000 = 103
=> 3x - 5 = 10
3x = 10 + 5 = 15
x = 15 : 3 = 5
Vậy x = 5
g) ( 5x - 15 ) 3 = ( 5x - 15 ) 7
=> (5x - 15 ) 3 : ( 5x - 15 ) 7 = 1
( 5x - 15 ) 3 - 7 = 1
( 5x - 15 ) -4 = 1 = 1-4 = -1-4
=> 5x - 15 = 1 hoặc 5x - 15 = -1
5x = 1 + 15 hoặc 5x = -1 + 15
5x = 16 hoặc 5x = 14
\(x=\frac{16}{5}\) hoặc \(x=\frac{14}{5}\)
Vậy, \(x\in\left\{\frac{16}{5};\frac{14}{5}\right\}\)
Cbht
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5^x+5^{x+1}+5^{x+2}+5^{x+3}=1+2+3+...+87+88-4^2\)
=>\(5^x+5^x\cdot5+5^x\cdot25+5^x\cdot125=88\cdot\dfrac{\left(88+1\right)}{2}-16\)
=>\(156\cdot5^x=44\cdot89-16=3900\)
=>\(5^x=\dfrac{3900}{156}=25\)
=>x=2
tương đương 5^x:25-5^x=600
tương đương 5^x:(25-1)=600
tương đương 5^x=600:24
tương đương 5^x=25
tương đương 5^x=5^2
tương đương x=2
vậy x=2
5\(^{x-2}\)- 5 \(^x\)= 600
5 \(^x\): 5 \(^2\)- 5 \(^x\)= 600
5 \(^x\)( 5 \(^2\)- 1 ) = 600
5 \(^x\)( 25 - 1 ) =600
5 \(^x\). 26 = 600
5 \(^x\) = 600 : 24
5\(^x\) = 25
5\(^x\) = 5 \(^2\)
=> x = 2
Vậy x = 2
~ Chúc bạn học tốt ~